2003
DOI: 10.1046/j.1365-2591.2003.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of ethylenediamine tetraacetic acid with sodium hypochlorite in aqueous solutions

Abstract: Ethylenediamine tetraacetic acid retained its calcium-complexing ability when mixed with NaOCl, but EDTA caused NaOCl to lose its tissue-dissolving capacity and virtually no free chlorine was detected in the combinations. Clinically, this suggests that EDTA and NaOCl should be used separately. In an alternating irrigating regimen, copious amounts of NaOCl should be administered to wash out remnants of the EDTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
0
27

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(195 citation statements)
references
References 25 publications
9
159
0
27
Order By: Relevance
“…In a literature review, it is mentioned that EDTA reduces the tissuedissolving effect of sodium hypochlorite which indicates the requirement of its use for a final rinse. 26,27 In this study, in terms of to reflect the clinical simulation, EDTA was applied following sodium hypochlorite irrigation for a final rinse which has found to be more effective in the removal of remaining root canal filling material when compared with the use of sodium hypochlorite alone or sodium hypochlorite combined with calcium hydroxide. remnants were significantly decrease at the cervical part of the root canals in favor of the EDTA and sodium hypochlorite group.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, it is mentioned that EDTA reduces the tissuedissolving effect of sodium hypochlorite which indicates the requirement of its use for a final rinse. 26,27 In this study, in terms of to reflect the clinical simulation, EDTA was applied following sodium hypochlorite irrigation for a final rinse which has found to be more effective in the removal of remaining root canal filling material when compared with the use of sodium hypochlorite alone or sodium hypochlorite combined with calcium hydroxide. remnants were significantly decrease at the cervical part of the root canals in favor of the EDTA and sodium hypochlorite group.…”
Section: Discussionmentioning
confidence: 99%
“…RC-Prep includes EDTA as a chelating agent [6] [7], which facilitates root canal preparation. Furthermore, urea peroxide is also included to generate oxygen in combination with sodium hypochlorite, which has potentially hazardous effects [8].…”
Section: Discussionmentioning
confidence: 99%
“…Grawehr et al found that a solution of EDTA mixed with NaOCl retained calcium-binding capacity, but showed a sudden and rapid decrease in the amount of chlorine in NaOCl, significantly reducing the ability of NaOCl to degrade tissue (21). Many mishaps, such as the splashing of NaOCl into the patient's or dentist's eye, damaging of the patient's clothes, extrusion of NaOCl beyond the apical foramen, inadvertent injection of irrigants instead of anesthesia, or allergic reaction to the irrigation solution, can occur during root canal treatment (22).…”
Section: Interactions Of Naoclmentioning
confidence: 99%